Polyphenols and miRNA interplay: a novel approach to combat apoptosis and inflammation in Alzheimer’s disease - Minji Zhou; Xiu'e Pang (Frontiers in Aging Neuroscience)
Alzheimer’s disease (AD) is a neurodegenerative condition associated with aging. As the population ages, the incidence of AD has risen annually, making it the fourth leading cause of death, following cardiovascular disease, cancer, and stroke. The main pathological features of AD are now thought to include the accumulation of extracellular amyloid-β (Aβ) plaques, the formation of intracellular neurofibrillary tangles, and a reduction in synaptic connections in the cerebral cortex and hippocampus. Polyphenols help protect against AD by influencing Aβ metabolism. Research has shown that polyphenols are particularly effective in reducing inflammation and inhibiting tumor necrosis factor-activated TNF-κB activity, indicating their significant pharmacological activity. MicroRNAs (miRNAs) play a role in regulating miRNA stability and inhibiting protein expression after transcription. They are prevalent in brain tissue and can specifically influence neuronal growth and the formation of synapses. The expression levels of miRNAs in the brains of AD patients significantly differ from those in healthy individuals of the same age. miRNAs have been recognized as potential biological markers and therapeutic targets for the early diagnosis of AD. It is important to note that polyphenols can influence gene regulation by affecting the expression of various miRNAs, suggesting a potential link between polyphenols, AD, and miRNAs. This review examines whether polyphenols impact the expression of APP and Aβ. Additionally, we explored whether the effects of polyphenols on APP and Aβ are related to miRNAs.